(untitled) (Experimental biology, 2026)
The study presents the advantages of utilizing saline raw materials from the southern region of Kazakhstan in the cosmetic industry. The southern region of Kazakhstan is rich in plant-based raw materials and saline lakes. Zhaksykylysh Lake, located near the Caspian Sea, covers an area of approximately 73 km² and holds an estimated 39 million tons of table salt reserves. A study on the physicochemical properties of the lake’s saline raw materials was conducted using high-precision instruments, including colorimetric analysis, FTIR spectroscopy, and X-ray diffraction methods. The results revealed that the majority of the salts consist of halide salts, with NaCl content ranging from 96,8±3,3%-to 98,4±2,4%. Additionally, small amounts of sodium sulfate (Na₂SO₄), calcium sulfate (CaSO₄·2H₂O), and sodium silicate (Na₂SiO₄) were detected. The composition analysis of the mud sampled from the lakebed showed a water content of 35-40%. The liquid phase contained the following ion concentrations: Na⁺ (1.90–18.12%), S²⁻ (25.65–44.30%), Ca²⁺ (1.12–2.13%), Mg²⁺ (3.85–4.21%), K⁺ (0.73–1.1%), carbonate ions (0.22–0.5%), and Cl⁻ (1.91–3.21%). Additionally, the absence of harmful substances in the composition makes these saline raw materials fully suitable for use as a raw material in cosmetic products. The combination of plant extracts native to the southern region of Kazakhstan with the saline raw materials from Zhaksykylysh Lake led to the development of the first seven cosmetic product prototypes. These included four types of salt blends for body exfoliation and three salt-based plant extract formulations designed to strengthen and deodorize the skin of hands and feet. The positive effects of these products on the skin confirmed the feasibility of fully utilizing saline raw materials in cosmetic production.